A preliminary study of the effects of macroeconomic variables on Singapore stock market. - Chye, Chia Chow. (2013)
This study aims to investigate the impact of various macroeconomic variables on equity returns. The return of the All-Singapore Share Index was used as the proxy for equity return in Singapore. Thirteen measures of various macroeconomic variables were used in this study.